Glycoproteins and Gal-GalNAc cause Cryptosporidium to switch from an invasive sporozoite to a replicative trophozoite. Issue 1 (January 2016) - Edwinson, Adam; Widmer, Giovanni; McEvoy, John
Graphical abstract: Highlights: Axenic culture was used to identify triggers of Cryptosporidium trophozoite development. Glycoproteins in FBS trigger trophozoite development in Cryptosporidium parvum and Cryptosporidium hominis . Glycoproteins in HCT-8 secretome enhance trophozoite development in C. parvum. Gal-GalNAc triggers trophozoite development and nuclear division. Abstract: The apicomplexan parasite Cryptosporidium causes cryptosporidiosis, a diarrheal disease that can become chronic and life threatening in immunocompromised and malnourished people. There is no effective drug treatment for those most at risk of severe cryptosporidiosis. The disease pathology is due to a repeated cycle of host cell invasion and parasite replication that amplifies parasite numbers and destroys the intestinal epithelium. This study aimed to better understand the Cryptosporidium replication cycle by identifying molecules that trigger the switch from invasive sporozoite to replicative trophozoite. Our approach was to treat sporozoites of Cryptosporidium parvum and Cryptosporidium hominis, the species causing most human cryptosporidiosis, with various media under axenic conditions and examine the parasites for rounding and nuclear division as markers of trophozoite development and replication, respectively. FBS had a concentration-dependent effect on trophozoite development in both species. Trophozoite development in C. parvum, but not C. hominis, was enhanced when RPMI supplemented with 10% FBS (RPMI-FBS) was conditioned by HCT-8 cells for 3 h. The effect of non-conditioned and HCT-8 conditioned RPMI-FBS on trophozoite development was abrogated by proteinase K and sodium metaperiodate pretreatment, indicating a glycoprotein trigger. Cryptosporidium parvum and C. hominis trophozoite development also was triggered by Gal-GalNAc in a concentration-dependent manner. Cryptosporidium parvum replication was greatest following treatments with Gal-GalNAc, followed by conditioned RPMI-FBS and non-conditioned RPMI-FBS ( P < 0.05). Cryptosporidium hominis replication was significantly less than that in C. parvum for all treatments ( P < 0.05), and was greatest at the highest tested concentration of Gal-GalNAc (1 mM).